Use of Reproductive Life Plans among Men and Women of Childbearing Age. Issue 1 (June 2015) - Byrnes, Lorraine
<x xml:space="preserve">Abstract</x> Poster Presentation Objective To describe knowledge, attitudes, and use of reproductive life plans (RLPs) and preconception care (PCC). Design Qualitative descriptive using a semistructured interview guide. Setting A large public, urban, college campus. Sample Male and female college students (N = 12) between ages 18 and 30. Methods Face‐to‐face interviews conducted by two researchers over an 8‐month period until saturation was achieved. Results Although the majority of participants in this study thought about and developed loosely structured plans about their reproductive future, there were many identified gaps in knowledge and utilization of RLPs. Four themes emerged from the gathered data: a formalized plan was an unfamiliar concept, initiation of a more formalized conceptualization was age dependent, developmental skills affected attitudes and use of RLPs, and sources of information (knowledge) were not based on evidence. Conclusion/Implications for Nursing Practice Findings suggest that knowledge, attitudes and use of RLPs are uncertain, at best. Clarifying the concept of RLPs is crucial to the development of health care interventions to promote knowledge and use of RLPs. Further studies should be conducted to assess the effect of RLPs on use of PCC and the reduction of unintended pregnancy. The RLP is a valid concept, but education and policy issues must be addressed to improve rates of use.